Analysis of risk factors for positive margins in robot-assisted laparoscopic radical prostatectomy with Retzius-sparing (RS-RARP) - Hua Yang; Bo Wu; Xuchang Liu; Kaiyuan Jia; Junyuan Bing; Yangjie Gao; Pengliang Shen; Xiaoming Cao (World Journal of Surgical Oncology)
Abstract Objective This study aims to analyze the risk factors for positive surgical margins following robot-assisted laparoscopic radical prostatectomy with Retzius-sparing (RS-RARP) to provide a basis for clinical preoperative evaluation and intraoperative decision-making. Methods A retrospective analysis was conducted on the clinical data of 103 patients who underwent RS-RARP at the First Hospital of Shanxi Medical University from May 2022 to May 2024. Patients were divided into positive margin and negative margin groups, as well as apical positive margin and apical negative margin groups based on surgical margin status. Patient demographics, preoperative data, and postoperative data were collected. Univariate and multivariate logistic regression analyses were used to evaluate the relationship between various factors and surgical margin status. Results A total of 103 patients were included, with 31 cases (30.1%) in the positive margin group and 72 cases (69.9%) in the negative margin group. The results of the Logistic Regression With Variable Reduction indicated that prostate volume (OR = 10.90, 95% CI: 3.49–34.04, p < 0.001) and ≥pT3 stage tumors (OR = 8.78, 95% CI: 2.54–30.42, p < 0.001) were independent risk factors for positive surgical margins. Additionally, they were also significantly associated with an increased risk of positive surgical margins at the prostate apex. Conclusion The study indicates that prostate volume and pT stage are notable predictors of positive surgical margins in RS-RARP.